Bioinspired Polymeric-based Core-shell Smart Nano-systems - Harwansh, Ranjit K.; Deshmukh, Rohitas; Barkat, Md A.; Rahman, Md. Akhlaquer (Pharmaceutical Nanotechnology, 2019)
Smart nanosystems (SNs) have the potential to revolutionize drug delivery. Conventional drug delivery systems have poor drug-loading, early burst release, limited therapeutic effects, etc. Thus, to overcome these problems, researchers have taken advantage of the host-guest interactions as bioinspired nanosystems which can deliver nanocarriers more efficiently with the maximum drug loading capacity and improved therapeutic efficacy as well as bioavailability. SNs employ nanomaterials to form cage molecules by entrapping new nanocarriers called smart nanosystems in their cargo and design. The activities of SNs are based on responsive materials that interact with the stimuli either by changing their properties or conformational structures. The aptitude of living systems to respond to stimuli and process information has encouraged researchers to build up integrated nanosystems exhibiting similar function and therapeutic response. Various smart materials, including polymers, have been exhaustively employed in fabricating different stimuli-responsive nanosystems which can deliver bioactive molecules to a specific site for a certain period with minimal side effects. SNs have been widely explored to deliver diverse kinds of therapeutic agents ranging from bioactive compounds, genes, and biopharmaceuticals like proteins and peptides, to diagnostic imaging agents for biomedical applications. Nanotechnology-based different nanosystems are promising for health care issues. The advancement of SNs with physical science and engineering technology in synthesizing nanostructures and their physicochemical characterization should be exploited in medicine and healthcare for reducing mortality rate, morbidity, disease prevalence and general societal burden.
Keywords: polymersomes